A novel analysis of LiCl solution regeneration experiments. (November 2022) - Tang, Chunli; Qian, Xiaoli; Tan, Ben; Yuan, Zhuoxi; Huang, Yingkai
Abstract: For the desiccant dehumidification, the regeneration process is a critical part. The paper experimentally investigated LiCl solution regeneration performance by analyzing the mass transfer characteristics. The regeneration rate, the regeneration potential and the concentration driving force were analyzed by considering the influence of independent variables such as the desiccant temperature, flowrate, and concentration. The regeneration potential, representing the underutilized mass transfer capacity stored in the outlet air, is determined by the smaller of the equilibrium value and the saturation humidity. The experimental results show the increase in solution temperature causes an increase in regeneration rate, accordingly also causes the regeneration potential and the residual driving forces to increase. It means that more regeneration potential is underutilized or ineffective capability exists. The increase in solution flowrate has no effect on the equilibrium curve. If the equilibrium humidity is less than the saturated humidity, the regeneration potential decreases with the increasing flowrate. Otherwise, it is necessary to consider special data to determine the variation trend. The increase in solution concentration causes a consistent decrease in regeneration rate, the regeneration potential and the residual driving forces.